Language Attitude Performed by First Generation of Javanese Transmigrants Towards ‘Unggah-Ungguh Basa’: A Study in Sungai Tenang Village, Jorong Mekar Jaya Sijunjung Regency West Sumatera - Destarini, Christie Septi; Jufrizal, Jufrizal (English Language and Literature, 2021)
This research aims to find out the language attitude of the first generations of the Javanese transmigrant in Jorong Mekar Jaya Sijunjung based on language loyalty, language pride and the awareness of the norm. This research was using both of quantitative and qualitative data (mixed method). the quantitative data were processed by using SPSS software program, then analyzed the qualitative data descriptively using the  language attitude theory of Garvin and Mathiot (1978)  The data were collected by questionnaires and interview which shared to 50 respondents. The results of this research shows that 98.52% first generation of the Javanese transmigrant who live in Jorong Mekar Jaya have highly positive language attitude towards unggah-ungguh basa.